Clinico-pathologic Study of Hemangioma of the Oral and Maxillofacial Region - Olatunde Oluleke Omisakin; Stephen Akau Kache; Kene Ifeanyi Aghadi (Medical Research and Its Applications Vol. 8, 2024)
Background: Oral and maxillofacial hemangioma is a benign vascular tumor that develops due to endothelial cell proliferation and occurs in and around the oral cavity. It consists of an abnormal overgrowth of tiny blood vessels. Hemangioma may not be present at birth but may appear at 6-month of life. It is a rare vascular tumor. Objective: To present the clinical presentation, modalities of treatment and surgical outcome of hemangioma of the oral and maxillofacial region. Materials and Methods: This is a retrospective study of all the patients that were treated from January 2009 to December 2023. Information was extracted from case files of patients. Data collected included: age at presentation, sex, location of the tumor, treatment given, findings and histological diagnosis. Results: Twenty- six cases of hemangioma were seen in the oral and maxillofacial region during the period of study. Twelve (n=12, 46.2%) were males and fourteen (n=14, 53.8%). Male to female ratio was 1.0 to 1.2. Cheek (46.2%) was the commonest site of occurrence, and the floor of the mouth was the least (3.8%). The age ranged from 4 months to 39 years. Our diagnostic tool was the aspiration of frank blood from the tumor which had similar clotting time with the normal blood and our mode of treatment included: injection of sclerosants and excision of the fibrous tissues. Conclusion: It is essential to treat the tumor as early as possible especially in large lesions with disfigurement or where it is complicated by hemorrhage or infection.